It's all relative : adventures up and down the world's family tree - Jacobs, A. J., 1968- (New York : Simon & Schuster, 2017)
Traces the author's three-year investigation into what constitutes family, describing how, after receiving an e-mail from a stranger who claimed to be a distant cousin, he embarked on an effort to build the biggest family tree in history.
Keywords: Jacobs, A. J., -- 1968- -- Family; Jacobs family; Jacobs, A. J., -- 1968- -- Family; Jacobs family; Genetic genealogy -- United States; Genealogy; Genetics